AIM2-driven inflammasome activation in heart failure - Onódi, Zsófia; Ruppert, Mihály; Kucsera, Dániel; Sayour, Alex Ali; Tóth, Viktória E; Koncsos, Gábor; Novák, Julianna; Brenner, Gábor B; Makkos, András; Baranyai, Tamás; Giricz, Zoltán; Görbe, Anikó; et al. (Cardiovascular research, 2021)
Abstract Aims Interleukin-1β (IL-1β) is an important pathogenic factor in cardiovascular diseases including chronic heart failure (HF). The CANTOS trial highlighted that inflammasomes as primary sources of IL-1 β are promising new therapeutic targets in cardiovascular diseases. Therefore, we aimed to assess inflammasome activation in failing hearts to identify activation patterns of inflammasome subtypes as sources of IL-1β. Methods and results Out of the four major inflammasome sensors tested, expression of the inflammasome protein absent in melanoma 2 (AIM2) and NLR family CARD domain-containing protein 4 (NLRC4) increased in human HF regardless of the aetiology (ischaemic or dilated cardiomyopathy), while the NLRP1/NALP1 and NLRP3 (NLR family, pyrin domain containing 1 and 3) inflammasome showed no change in HF samples. AIM2 expression was primarily detected in monocytes/macrophages of failing hearts. Translational animal models of HF (pressure or volume overload, and permanent coronary artery ligation in rat, as well as ischaemia/reperfusion-induced HF in pigs) demonstrated activation pattern of AIM2 similar to that of observed in end-stages of human HF. In vitro AIM2 inflammasome activation in human Tohoku Hospital Pediatrics-1 (THP-1) monocytic cells and human AC16 cells was significantly reduced by pharmacological blockade of pannexin-1 channels by the clinically used uricosuric drug probenecid. Probenecid was also able to reduce pressure overload-induced mortality and restore indices of disease severity in a rat chronic HF model in vivo. Conclusions This is the first report showing that AIM2 and NLRC4 inflammasome activation contribute to chronic inflammation in HF and that probenecid alleviates chronic HF by reducing inflammasome activation. The present translational study suggests the possibility of repositioning probenecid for HF indications. Graphical Abstract